Data on the web best practices: Portal Dados Abertos Capes analysis - Torino, Emanuelle [UNESP]; Vidotti, Silvana Aparecida Borsetti Gregorio (Universidade Federal da Paraíba, 2021)
The present study aimed to discuss the attendance of government open datasets related to the Stricto Sensu Graduate Evaluation available in the portal Dados Abertos Capes to data on the web best practices. The analysis presented the adequacy of the 29 data sets to the 35 data on the web best practices, recommended by the World Wide Web Consortium, as well as the benefits achieved by the attendance, in order to provide theoretical contributions from Information Science to support the data providers, with regard to improving the data made available on the web. From the analysis it was possible to verify, of the 35 best practices, 7 do not apply to the analyzed datasets; 20 were considered did not met or partially met and 8 considered met. The data available on the portal Dados Abertos Capes need adjustments to be able to meet the third star of open data.
Boas práticas para dados na web: Análise do portal Dados Abertos Cape
Keywords: Access to information law; Data on the web best practices; Government open data